Mechanism and inhibition efficiency of biomass Tetraselmis chuii sp. on carbon steel corrosion in the environment under the conditions of oil wells - Yayan - Sunarya; Heli Siti H; Munawaroh Munawaroh; Gun Gun Gumilar (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
Corrosion control on petroleum pipe wells can only be done through the addition of corrosion inhibitors. In this study, the corrosion inhibitors studied were sourced from marine microorganisms, namely the type of microalgae Tetraselmis chuii sp. The aim to be achieved in this study was to determine the mechanism and efficiency of inhibition of the extraction of microalgae biomass in corrosion of carbon steel in an environment of petroleum conditions. To achieve this goal, a potentiodynamic polarization method (Tafel extrapolation) was used and the Electrochemistry Impedance Spectroscopy (EIS) method used the galvanostat-potentiostat device (Voltalab 40, PGZ 301). The results obtained from this study indicate that API 5L X65 carbon steel in the petroleum environment is very significantly corroded, caused by acidic media derived from acetic acid and dissolved CO2. The inhibition ability of the Tetraselmis chuii sp. Biomass extract. in line with the increasing extraction concentration reaching optimum at a concentration of 250 ppm with inhibition efficiency reaching 70%. The mechanism of inhibition takes place through the formation of a protective layer adsorbed on the surface of carbon steel. The protective membrane formed is uneven and tends to be porous.